Resilience Engineering: Learning to Embrace Failure. (Communications of the ACM, 2012)
An interview is presented with computer programmers Jesse Robbins, John Allspaw, Kripa Krishnan. It focuses on GameDay, a computer program created by online retailer Amazon that intentionally inserting major failures in to critical systems to indicate areas of concern or that needed improvement. Robbins discussed creating the program, while Allspaw and Krishnan address similar programs at Internet services provider Google and online commerce company Etsy.